Chronic active Epstein-Barr virus-associated secondary hemophagocytic lymphohistiocytosis in pregnancy: a case report - Masaya Takahashi; Shintaro Makino; Hiroko Iizuka; Masaaki Noguchi; Koyo Yoshida (BMC, 2021)
Abstract Background Secondary hemophagocytic lymphohistiocytosis (sHLH) is a rare and fatal disease characterized by uncontrolled immune cell activation that can lead to a cytokine storm. Unfortunately, this condition can occur even during pregnancy, threatening both maternal and fetal lives. Case presentation A 23-year-old nulliparous woman at 26 weeks of gestation presented with continuous fever, coughing, and sore throat. Upon arrival at our hospital, her temperature was >38°C and laboratory findings indicated cytopenia (neutrophil count, 779/μL; hemoglobin level, 10.2 g/dL; platelet count, 29,000/μL), elevated ferritin level (1,308 ng/mL), and elevated soluble interleukin-2 receptor level (11,200 U/mL). Computed tomography showed marked splenomegaly. Bone marrow examination revealed hemophagocytosis, and blood examination showed a plasma Epstein-Barr virus (EBV) DNA level of 8.9 × 105 copies/μg. The monoclonal proliferation of EBV-infected T cells was confirmed by Southern blotting, and the patient was diagnosed with chronic active EBV-associated sHLH and T-cell lymphoproliferative disease. Immediately after admission, the patient's condition suddenly deteriorated. She developed shock and disseminated intravascular coagulation, requiring endotracheal intubation along with methylprednisolone pulse and etoposide therapy. Although the patient recovered, she delivered a stillborn baby. After delivery, she was treated with reduced-dose dexamethasone, etoposide, ifosfamide, and carboplatin (DeVIC) and steroid (dexamethasone), methotrexate, ifosfamide, L-asparaginase, and etoposide (SMILE) chemotherapies. Five months after diagnosis, she received human leukocyte antigen-haploidentical allogeneic bone marrow transplantation from her sister. She remains in remission for 5 months from the time of transplantation to the present. Conclusions sHLH, which may cause maternal and fetal death, should be carefully considered in critically ill pregnant women, particularly those presenting with continuous fever and cytopenia.